Milled graphite as a pertinent analogue of French UNGG reactor graphite waste for a CO2 gasification-based treatment. (May 2015) - Pageot, J.; Rouzaud, J.-N.; Ali Ahmad, M.; Deldicque, D.; Gadiou, R.; Dentzer, J.; Gosmain, L.
Abstract: Graphite has been used in gas-cooled nuclear reactors as a neutron moderator. The dismantling of nuclear reactors will generate significant amounts of graphite waste. Neutron irradiation is responsible for 14 C formation in graphite, and it leads to severe structural and nanostructural degradations. At high neutron fluence, nanoporous turbostratic carbon is formed from original lamellar graphite. This phase is supposed to be especially 14 C enriched. An original 14 C extraction process was proposed: to "decontaminate" graphite waste from 14 C by selectively gasifying such degraded areas, without entirely consuming the graphite waste. To specify the operating conditions, milled graphite was used as a nonradioactive analogue. Raman microspectrometry and transmission electron microscopy techniques show that neutron irradiation and milling lead to similar multiscale organization, and especially nanoporous carbon formation. Thermogravimetry experiments were then carried out between 800 and 1100 °C, at a CO2 pressure of 0.1 MPa. To determine the best temperature range allowing a nanoporous component selective gasification, Raman microspectrometry analysis was coupled with transmission electron microscopy observations on the residues obtained for each gasification temperature. The 950–1000 °C temperature range is the most efficient allowing a complete elimination of degraded areas supposed to be representative of nuclear graphite waste 14 C-rich areas.